Nicolau syndrome with pemphigus vulgaris: a rare case report and review of literature - Deepthi Avvaru; Soumya Patil; Bhavana Doshi; Shashikala Wali (SpringerOpen, 2023)
Abstract Background Nicolau syndrome is a rare adverse drug reaction clinically presented with painful erythema and tissue necrosis often accompanied by intramuscular injections of NSAIDS (diclofenac), penicillin, corticosteroids and local anesthetics. Case presentation This case report describes a 29-year-old male patient who was repeatedly hospitalized for the treatment of recalcitrant pemphigus vulgaris. When the patient visited for the fourth time to our hospital, he complained of unusual sharp pain over the right gluteal region ever since the administration of diclofenac 75 mg intramuscular injection for persistent back pain during his previous stay. On physical examination, the right gluteal region showed a globular swelling with erythema and pus filled necrosed tissue. The CT scan did not show any presence of hematoma, ruling out any possibility of compartment syndrome. Based on this clinical evidence he was diagnosed with Nicolau Syndrome secondary to diclofenac injection. The tissue injury necessitated surgical debridement and after a span of 2 months, it healed leaving a permanent scar. In addition, this case report highlights the treatment of recalcitrant pemphigus vulgaris with rituximab therapy. Conclusion Clinical pharmacist plays a vital role in educating healthcare professionals about following right protocol for administration of injectable drugs, early detection and management of the ADR. Similarly, patient receiving injections should be educated about warning signs and symptoms of such adverse drug reaction.